Meta-Analysis of Students’ Critical Thinking Skills Improvement on Physics Learning - Nurul Hikmah; Mukhayyarotin Niswati Rodliyatul Jauhariyah (Berkala Ilmiah Pendidikan Fisika, 2021)
Critical-thinking skill is one of the 21st-century abilities that students must have. This study aimed to analyze the critical thinking abilities to improve physics learning that was reviewed: overall, learning model, education level, subject matter, and the media used. This research method used meta-analysis. The meta-analysis research stage was to determine the research topic, decide data selection criteria, search for data, visualize VOSviewer, classify data information, calculate the effect size, and then analyze the data and conclude. The data collection technique used secondary data from previous research of 18 scientific publication articles. The data analysis technique used the effect size. This meta-analysis concluded that critical-thinking skills significantly influence physics learning, with an average effect size of 1.33 and an influence of 90%. Critical thinking skills in learning physics can significantly affect vocational education with the cooperative-learning time-token type model, using the subject of static fluid, and assisted by real learning media using a puzzle.